Approximations for Large Deflection of a Cantilever Beam under a Terminal Follower Force and Nonlinear Pendulum. (7th March 2013) - Vázquez-Leal, H.; Khan, Y.; Herrera-May, A. L.; Filobello-Nino, U.; Sarmiento-Reyes, A.; Jiménez-Fernández, V. M.; Pereyra-Díaz, D.; Perez-Sesma, A.; Castaneda-Sheissa, R.; Díaz-Sanchez, A.; Huerta-Chua, J.
Abstract : In theoretical mechanics field, solution methods for nonlinear differential equations are very important because many problems are modelled using such equations. In particular, large deflection of a cantilever beam under a terminal follower force and nonlinear pendulum problem can be described by the same nonlinear differential equation. Therefore, in this work, we propose some approximate solutions for both problems using nonlinearities distribution homotopy perturbation method, homotopy perturbation method, and combinations with Laplace-Padé posttreatment. We will show the high accuracy of the proposed cantilever solutions, which are in good agreement with other reported solutions. Finally, for the pendulum case, the proposed approximation was useful to predict, accurately, the period for an angle up to 179 .99999999 ∘ yielding a relative error of 0.01222747.